Ampliﬁcation of Complete HIV-1 Envelope Genes from Puriﬁed CD4+ T Cell Populations - Jiao, Yanmei; Li, Juan; Hua, Wei; Gao, Yanqing; Zhang, Tong; Wu, Hao (North American Journal of Medicine and Science, 2009)
Polymerase chain reaction (PCR) ampliﬁcation of full-length HIV-1 envelope genes directly from uncultured clinical samples or from plasma of HIV patients using RT-PCR or from peripheral blood mononuclear cells (PBMC) DNA extracts of HIV patients is difﬁcult. As HIV mainly infected CD4 positive cells, this paper first describes a sensitive method for the amplification of full-length HIV-1 envelope genes from purified CD4+ cells, and compares this method with other, less effective, procedures. This method were suitable for ampliﬁcation of HIV-1 envelope genes directly from clinical samples especially from those of low viral load.